Security risk analysis approach for smart grid. (2018) - Yadav, Dharmendra; Mahajan, Anjali R.; Thomas, A.
The paper comprehensively defines the effective research from the correspondence sources examines to assess the risk that is connected to smart grid systems. The research gives a defined framework like of smart grid network have fizzled in light of an absence of appropriate risk assessment from the beginning. This study is focused on evaluating the risk posed to a system like smart grid while providing solutions that will help to curb the risk. The qualities of a well-designed system is be evaluated so as the standard measure for a properly functional grid. The threats posed to the system as a software and as a network will be discussed and backed up by the previous study. The solutions to the grid's security framework are provided for each vulnerability. The paper gives the solutions and recommendations that apply to systems of the same nature.